Against all odds. The role of contingency in Chavez and the Bolivarian movement’s path to power in Venezuela - Gauna PH. D., Aníbal (2023)
This article makes emphasize in the effect of contingency in the emergence of Chavez and the Bolivarian movement, through the micro-structuring of his path to power. Based on interviews to key actors conducted by journalists and historians, we present an analytical history of five contingency dynamics: the positive impact on public opinion of the February 1992 coup, the formation of a singular revolutionary coalition, the mishaps by the military intelligence, the chance given to Chavez to redeem his the military failure, and the political system’s openness to electoral outsiders. We conclude that there were five elements that paved this path: the movement’s leadership strategy, the tree with three roots, the esprit de corps within the Armed Forces, Hugo Chavez network, and the radicalization of factionalism in the party system.